Evaluation of the Antimicrobial Potentials of Selected Nut Extracts on Pathogenic Bacteria and Mycotoxigenic Fungi - Modupeade C. Adetunji; Anuoluwapo N. Popoola; Oluwafemi Segun Aina (Biology, Medicine, & Natural Product Chemistry, 2026)
The antimicrobial potential of nut extracts has garnered interest due to their nutritional benefits and bioactive compounds. This study evaluated the ethanoic extracts of walnut (Tetracarpidium conophorum), almond (Prunus dulcis), and “abere” (Picralima nitida) for inhibitory effects against various pathogenic bacteria, including Escherichia coli, Staphylococcus aureus, Salmonella typhi, Klebsiella pneumoniae, Shigella spp., and mycotoxigenic fungi such as Aspergillus flavus and Aspergillus fumigatus. In-silico analyses provided further insights into the bioactive compounds identified through GC-MS, focusing on their drug-likeness and toxicity profiles. Two key compounds from P. nitida - Diethylphthalate (A1) and 3-oxo-2-pentyl-methylcyclopentaneacetic acid (A3) - demonstrated promising drug-like properties, with A1 being non-toxic and A3 showing mild carcinogenic potential. Molecular docking studies highlighted the extracts’ potential as inhibitors against Mycobacterium tuberculosis and Dengue virus targets, with some extracts outperforming the reference drugs isoniazid and acetaminophen, although none surpassed ampicillin. This study underscores the importance of further research to isolate specific bioactive components, optimize extraction techniques, and explore the full antimicrobial potential of these nut extracts. Future studies should also consider the concentration, extraction methods, and target microorganisms to enhance the understanding of their antimicrobial efficacy.